The effect of COVID‐19 epidemic on the sexual function of healthcare professionals - Bulut, Ender Cem; Ertaş, Kasım; Bulut, Dilek; Koparal, Murat Yavuz; Çetin, Serhat (Andrologia, 2021)
Studies have shown that healthcare professionals struggling with epidemics develop symptoms of post‐traumatic stress disorder. The aim of this study is to show how often and severely erectile dysfunction, one of the components of post‐traumatic stress disorder, is seen among healthcare professionals during COVID‐19 outbreak. The Impact of Event Scale‐Revised (IES‐R) and the Index of Erectile Function‐5 (IIEF‐5) were applied to 159 male healthcare professionals working in COVID‐19 units and a control group of 200 people. Healthcare professional group was divided into subgroups according to occupation (physician, nurse), age‐group (18–25, 26–30, >30), marital status and unit of work (Suspected Patient Area, Diagnosed Patient Area). Both stress disorder and erectile dysfunction were seen at higher rates in healthcare professionals group (p < .001). The median IIEF‐5 scores of nurses, married subjects and those working in the Diagnosed Patient Area, were found to be higher (p < .001, p = .014, p = .011 respectively). During the COVID‐19 outbreak, healthcare professionals are exposed to psychological trauma and their sexual function may be negatively affected. The measures to be taken are important to estimate which groups are more affected.